220k views
4 votes
Helppp!!!! please!!!

Helppp!!!! please!!!-example-1

1 Answer

3 votes

Answer:

Option B is the correct answer

Explanation:

Center of the circle lie on point (-1, - 3) = (h, k)


\implies \: h = - 1 \: \: k = - 3 \\radius \: r \: = 2 \\ equation \: of \: circle \: in \: standard \: form \: \\ is \: given \: as : \\ {(x - h)}^(2) + {(y - k)}^(2) = {r}^(2) \\ {(x + 1)}^(2) + {(y + 3)}^(2) = {2}^(2) \\ \purple{ \boxed{ \bold{ {(x + 1)}^(2) + {(y + 3)}^(2) = 4}}}

User Anthoni
by
4.7k points